AD, Volume 48, n° 1, 2023 - Full Issue - Journal System, (Africa Development, 2023)
Contents Editorial Note....................................................................................v Note éditoriale.......................................................................ix ‘‘Cabo Verde à beira da revolução”: a emergência do pan-africanismo cabo-verdiano e os protestos em África Redy Wilson Lima & Stephanie Duarte Vicente ........................................ 1 Why Nigerian Agbada Fabric is (often) Imported, while Indian Sari Fabric is Local: A Comparative History of Textile Manufacturing Yarri B. Kamara .............................................................27 Communal Governance and Transnationalism: A Case Study of the Nigerien Forex Trading Community in Benin City Martha Sambe, Oreva Olakpe & Rafeeat Aliyu .......................................55 Towards a Bottom-up Approach for Localising SDGs in African Cities Findings from Cairo and Dar es Salaam Omar Nagati, Hanaa Gad, Amin Ali El-Didi, Jacob M. Kihila, Elinorata Mbuya & Emmanuel Njavike.............................................79 A ‘Chinese’ Street (Un)Scripted and (Re)Imagined: Material Shifts, City-Making and Altered Ways of Living in Suburban Johannesburg Romain Dittgen, Gerald Chungu & Mark Lewis..............................................113 The De-territorialization on Egypt’s Desert Cities: The Case of Sixth of October City Deena Khalil .....................................................141 « L’histoire de l’eau » et la dynamique politique, sociale et culturelle du nord du Cameroun Sambo Armel...............................................163 La RSE stratégique dans le secteur minier au Sénégal : incubateur d’inclusion de genre et de développement communautaire ? Bakary Doucouré ............................................187 Effective Knowledge Transmission and Learning in Agriculture: Evidence from a Randomised Training Experiment in Ethiopia Hiwot Mesfin, Yohannis M. Tessema, Nyasha Tirivayi & Eleonora Nillesen............................................213